The Outcome of a Double Mesh Intra Peritoneal Repair for Complex Central Hernia. A Retrospective Cohort Study (Medical Forum Monthly, 2024)
Objective: The outcome of a double mesh intra peritoneal repair for complex central hernia. a retrospective cohort study.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the SMBB Medical College Lyari and Sindh Government Lyari General Hospital, Karachi from January 2016 to January 2018.Materials and Methods: The data has been collected from previous records for a period of 2 years. There were n=110 patients. All the patients with ventral hernias were included from age of greater than 20years to 70years with both genders included. The patients who were excluded were women with pregnancy, bleeding disorders.Results: Out of 110 patients enrolled there were 42 males and 68 females. Male to female ratio was 1:1.6. the mean age of patient was 44.82 ±6.29 years Mostly the age range of patients were >50yrs in males and in females <50yrs. The mean BMI of patients were > 30kg/m2. There were 30 (27.2%) patients reported with recurrent ventral hernias with associated multiple comorbidities. The n=22 (20%) patients reported with surgical site wound infections which resolved on follow up. No mortality was reported in our enrolled cases.Conclusion: Double mesh repair is an effective method with an associated decreased recurrence and postoperative complications.